Preparation and Characterization of (SBA-15)-(p-Methyldibromoarsenazo) Composite Material - Li, Jing-Mei; Wang, Qi; Zhai, Qing-Zhou; Zou, Ming-Qiang (Asian Journal of Chemistry, 2010)
Mesoporous SBA-15 molecular sieve was prepared under a strong acidic condition by using triblock copolymer poly(ethylene glycol)- block-poly(propylene glycol)-block-poly (ethylene glycol) as template. The composite material (SBA-15)-(p-methyldibromoarsenazo) was prepared by embedding p-methyldibromo-arsenazo into the pores of the SBA-15 by liquid grafting method. By means of chemical analysis, powder X-ray diffraction, Fourier transform infrared spectroscopy, lowtemperature nitrogen adsorption-desorption technique, UV-Vis solid state diffuse reflectance absorption spectroscopy and luminescence studies, the composite material was characterized. The results showed that the guest was sucessfully encapsulated in the channels of the SBA-15.